Teacher emotional agency appropriating the learning management system in the midst of the pandemic - Romerosa, Peter G.
This study examines how teacher emotional agency is achieved in the appropriation of the Learning Management Systems (LMS) policy of a non-sectarian private institution in an urban area during the COVID-19 pandemic. It uses digital ethnography or ethnographic work in a digital environment by making an informed description of an event involving teachers as the primary interlocutors or participants of the study. Primarily, the ethnography utilizes observation, participants observation, interview, and document analysis to generate data and meet the study's primary objectives, which is to examine how online distance learning via the learning management system is appropriate through teacher emotional agency amid the pandemic.